TEACHING DESCRIPTIVE TEXT WRITING BY USING ATTRIBUTE LISTING TO SMK - Karsinah, .; Sada, Clarry; ., Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: The aim of this research is to investigate the effectiveness of teaching descriptive text writing by using attribute listing technique to the tenth grade students of Marketing program of SMK Negeri 3 Pontianak in academic year 2014/2015. This research was done by conducting a pre experimental study which consists of pretest, posttest and three times of treatments. The sample of this research is class X Marketing 2 and the total of the students is 34. The data had been collected by measurements techniques. The tool of data collecting was writing test. The finding of the research showed that the mean score of students? pretest was 51.12 while the posttest was 76.18. The students? achievement was increased by the different score between pretest and posttest was 25.03. The was higher than the (16.69>2.042 at ? 5%). The result of the effect size (ES) was 2.86. It means that teaching descriptive text writing by using attribute listing technique to the tenth grade students of Marketing Program of SMK Negeri 3 Pontianak is categorized as highly effective with the Effect Size (ES) > 0.8 (2.86 > 0.8). Keywords: Attribute Listing, Descriptive Text Abstract: Penelitian ini bertujuan untuk mengetahui efektivitas pengajaran menulis teks deskriptif dengan menggunakan teknik attribute listing pada siswa kelas X jurusan Pemasaran di SMK Negeri 3 Pontianak tahun ajaran 2014/2015. Penelitian ini di lakukan dengan menerapkan pre experimental study yang terdiri dari pretest, posttest dan treatments. Sampel dalam penelitian ini adalah siswa kelas X Pemasaran 2 yang berjumlah 34 siswa. Data yang di kumpulkan menggunakan teknik pengumpulan data. Alat pengumpulan data adalah writing test. Hasil analisis data menunjukan bahwa skor rata-rata dari pretest siswa adalah 51,12 sedangkan posttest adalah 76.18. Prestasi siswa meningkat dengan perbedaan skor antara pretest dan posttest 25,03. lebih tinggi dari pada (16.69>2.042 pada ? 5%). Hasil Effect Size (ES) adalah 2.86. hal tersebut menunjukan bahwasannya mengajarkan menulis teks deskripsi dengan menggunakan teknik attribute listing pada siswa kelas X jurusan Pemasaran di SMK Negeri 3 Pontianak di kategorikan sangat effektif dengan tingkat efektivitas (ES) > 0.8 (2.86 > 0.8). Kata Kunci: Attribute Listing, Teks Deskriptif